2003
DOI: 10.1093/humupd/dmg003
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor gene and male infertility

Abstract: Androgens are critical steroid hormones that determine the expression of the male phenotype. Their actions are mediated by a single androgen receptor (AR) which, upon ligand binding, translocates to the nucleus to regulate the expression of androgen-responsive genes. Mutations that disrupt AR function totally result in the complete feminization of 46 XY individuals and the complete androgen insensitivity syndrome. Studies have revealed that AR mutations that do not lead to complete abrogation of its activity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
71
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 55 publications
0
71
0
8
Order By: Relevance
“…Thus the majority of infertile cases remain unexplained. Mutations in the AR gene, including variation in the number of CAG repeats, have been found to be associated with male infertility in some populations but not others (Yong et al, 2003). AR-GGN repeat length polymorphism has been less studied in male infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the majority of infertile cases remain unexplained. Mutations in the AR gene, including variation in the number of CAG repeats, have been found to be associated with male infertility in some populations but not others (Yong et al, 2003). AR-GGN repeat length polymorphism has been less studied in male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…The CAG repeat has been well studied in a variety of medical conditions in addition to male infertility (Hickey et al, 2002;Sasaki et al, 2003;Yong et al, 2003). Expansion of the CAG repeat above the normal range has been found to be associated with adult onset of spinal and bulbar muscular atrophy (La Spada et al, 1991), characterized by undermasculinization and progressive neuromuscular degeneration.…”
mentioning
confidence: 99%
“…Androgen and estrogen exert their cellular effects via steroid receptors (ARs and ERs, respectively) of the nuclear receptor superfamily and act as ligand-dependent transcription factors [26]. After the binding of androgens, ARs undergo a conformational change, dimerization, translocation to the cell nucleus and binding to specific DNA sequence, thus modulating expression of target genes [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in vitro have demonstrated that CAG repeat number shows an inverse correlation with AR activity [9][10][11][12][13][14]. Hence, it's not difficult to understand that shorter CAG repeats, increasing AR activity, are associated with prostate cancer [15,16], hirsutism [17] and hyperandrogenism in ovary [18,19], while longer CAG repeats, decreasing AR activity, are related to hypoandrogenicity [20] and male infertility due to impaired sperm production [10,21]. CAG tracts beyond the normal range (>40 CAG repeats) leads to Kennedy's syndrome, a fatal neuromuscular disease [22].…”
Section: Introductionmentioning
confidence: 99%